2014
DOI: 10.4236/ojoph.2014.41005
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Interleukin-6 (IL-6) Level Is a Marker for Treatment Resistance to Bevacizumab in Age-Related Macular Degeneration —Aqueous Cytokines after Bevacizumab

Abstract: Background: To prospectively evaluate the effect of intravitreal bevacizumab on aqueous levels of interleukin-6 (IL-6) and vascular endothelial growth factor (VEGF) in patients with exudative age-related macular degeneration (AMD) and to correlate clinical outcomes of patients and aqueous cytokine levels before and after injection. Methods: The study group consisted of 30 eyes from 30 patients with exudative AMD who underwent intravitreal injection of bevacizumab three times at monthly intervals. The aqueous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Topical administration (as opposed to intravitreal injection) may reduce the risk for adverse events, such as endophthalmitis, infection, and eye irritation. Finally, a study by Chalam et al 62 found that interleukin 6 levels correlate with resistance to anti-VEGF treatment in AMD, further increasing the need for alternative interventions. Taken together, topical minocycline and/or DAM eye drops may represent a promising new treatment strategy for CNV-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Topical administration (as opposed to intravitreal injection) may reduce the risk for adverse events, such as endophthalmitis, infection, and eye irritation. Finally, a study by Chalam et al 62 found that interleukin 6 levels correlate with resistance to anti-VEGF treatment in AMD, further increasing the need for alternative interventions. Taken together, topical minocycline and/or DAM eye drops may represent a promising new treatment strategy for CNV-related disorders.…”
Section: Discussionmentioning
confidence: 99%